Design of Matching Circuit Transformer for High-Power Transmitter of Active Sonar - Song, Seung-Min; Kim, In-Dong; Lee, Byung-Hwa; Lee, Jeong-Min (Journal of electrical engineering & technology, 2020)
Generally, transducers for active sound navigation and ranging (SONAR) has a low power factor due to large capacitive load characteristics. Thus, high-power transmitter requires an impedance matching circuit to improve the low-power factor of a transducer. Conventional matching circuits composed of L and C elements have many additional lumped elements. In addition, transducers for active sonar have numerous channels. As a result, the implementation of the matching circuit with many devices is non-practical and bulky due to spatial limitations. Therefore, this paper proposes a new matching circuit that uses the magnetization inductance of the transformer without additional elements. In addition, a design method of a transformer that implements a matching circuit using magnetization inductance is proposed. The proposed matching circuit is verified by the experimental results, and the volume and weight are reduced by approximately 20% compared to the conventional matching circuit.